IOT Pada Purwarupa Sistem Keamanan Pintu Kantor Dengan Sensor RFID dan PIR Berbasis Telegram - Suci Br Kembaren; Elsadora Haroannauli Patricia Br Gurning; Any Kurniawaty Yapie (Pusat Riset dan Inovasi Nasional, 2023)
The proposed office door security system combines RFID (Radio-Frequency Identification) Sensor and PIR (Passive Infrared) Sensor technology with Telegram-based communication. The design of this system requires RFID and PIR sensors to be formed in order to produce a system design that is made to meet the needs of system users. The aim of this system is to increase the security level of access to office space by combining identification of access owners via RFID cards and motion detection using PIR sensors. Communication through the Telegram platform is used to provide real-time notifications to access owners when there is activity at the office door. The control system for this device is controlled by the Esp32 Microcontroller, using 4 inputs, namely Rfid, PIR, Keypad and telegram sensors, as well as 5 outputs, namely Selenid Doorlock, Buzzer, LCD, Relay and telegram. By using the esp32 microcontroller to process data and the telegram application for IoT as a link between devices and smartphones. With 2 sensors as logic inputs for the esp32 microcontroller, the number of outputs that occur is 5, namely in the form of a sound from a buzzer as a warning, and a PIR as a sensor to open the door from the inside. When opening the RFID with a card tag, then the selenoid doorlock will open. Overall, the design of this office door security system has the potential to improve security and monitoring in the office space. By combining the technology of RFID sensors, PIR sensors and Telegram-based communication, this system enables accurate identification, real-time motion detection and fast interaction between the security system and the access owner. So that Telegram is successful in sending notifications if someone enters, that is, they will appear.